INTEGRATED ISLAMIC SCHOOL QUALITY IMPROVEMENT MANAGEMENT - Hidayatulloh, Faruqi; Siti Patimah; Andi Warisno; Nurul Hidayati Murtafiah (Cakrawala Pedagogik, 2024)
Integrated Islamic Schools have great potential to become superior educational institutions. This article discusses strategies and programs to improve the quality of education in Integrated Islamic Schools, including: Improving the quality of the curriculum, teachers and learning environment, strengthening competitiveness, increasing accountability and transparency, building a culture of quality, increasing efficiency and effectiveness. The implementation of these strategies and programs must be adapted to the conditions of each Integrated Islamic School. Commitment and cooperation from all parties is required, as well as involving external parties if necessary. With continued efforts, Integrated Islamic Schools can become quality educational institutions and provide benefits to society.